2015
DOI: 10.1002/2015gl065736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geographic‐geomagnetic pole offset on ionospheric outflow: Can the ionosphere wag the magnetospheric tail?

Abstract: The generalized polar wind model was used to simulate the polar ionosphere during the September/October 2002 storm. The solar terminator moved across the polar caps in a diurnal oscillation during this equinox period. The main conclusions of this study are the following: (1) the terminator oscillation generates a diurnal oscillation in the total hemispheric fluxes of the polar wind from the ionosphere into the magnetosphere; (2) the diurnal oscillation of outflow in the Northern Hemisphere is 12 h out of phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Heating due to solar illumination changes the scale height of the ionosphere and enables ionospheric outflow (Maes et al, 2015). As solar illumination is modulated by the geomagnetic dipole, the dipole tilt angle also plays an important role in cold ion outflow (e.g., Barakat, Eccles, & Schunk, 2015;Kitamura et al, 2011). In addition, simulations by Cnossen and Richmond (2012) suggest that the dipole tilt angle modulating the efficiency of solar wind-magnetosphere coupling could influence Joule heating in the polar ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Heating due to solar illumination changes the scale height of the ionosphere and enables ionospheric outflow (Maes et al, 2015). As solar illumination is modulated by the geomagnetic dipole, the dipole tilt angle also plays an important role in cold ion outflow (e.g., Barakat, Eccles, & Schunk, 2015;Kitamura et al, 2011). In addition, simulations by Cnossen and Richmond (2012) suggest that the dipole tilt angle modulating the efficiency of solar wind-magnetosphere coupling could influence Joule heating in the polar ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…During geomagnetic storms, which occur more frequently in the equinoctial months, more energy is deposited from the magnetosphere. The large offset between the geographic and geomagnetic poles could facilitate the coupling between the ionosphere‐magnetosphere and the solar wind and probably induce a stronger response of plasma drifts to external drivers during geomagnetic storms (Ridley et al, ; Barakat et al, ; Bruinsma et al, ). When IMF B Z is southward ( B Z < 0), the upward ion drifts in the two hemispheres vary oppositely when the direction of IMF B Y component changes (Figure ), this is also consistent with the Svalgaard‐Mansurov effect.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Based on measurements from the Fast Auroral Snapshot satellite, Zhao, Jiang, Ding, et al () found that H + upflow intensity is stronger in the NH during geomagnetically quiet times, whereas its enhancement during disturbed times is more dramatic in the SH than that in the NH. In addition, Barakat et al () simulated asymmetrical diurnal variation of the ionospheric ion outflow fluxes and discussed possible contributions of the asymmetric magnetic field between the two hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Barakat et al [] used the generalized polar wind model to simulate ionospheric outflow during the 28 September 2002 storm, close to equinox conditions. They focused on the effects of the offset between the geographic and the magnetic axes on the ionospheric ion outflow into the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the disturbance dynamo intensity as a function of UT and season and found significant variation in the magnitude of these electric fields for similar activity levels. Barakat et al [2015] used the generalized polar wind model to simulate ionospheric outflow during the 28 September 2002 storm, close to equinox conditions. They focused on the effects of the offset between the geographic and the magnetic axes on the ionospheric ion outflow into the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%